Current Trends in Endodontic Clinical Practice in Tripoli, Libya: A Cross-Sectional Study - Farouk Ben Fadl,; Sumaya Aghila,; Mohamed Ben Hakoma,; Mohamed Jedeh, (AlQalam Journal of Medical and Applied Sciences, 2025)
Root canal therapy (RCT) is typically performed in Tripoli, Libya, by general dental practitioners (GDPs), who are more widely available and less expensive than endodontists. Concerns have been expressed about the quality of RCTs performed by GDPs, presumably due to a lack of equipment or experience, so this study aims to evaluate current endodontic practices in Tripoli, Libya. A cross-sectional study was conducted using a questionnaire distributed to 250 randomly selected Libyan dentists in Tripoli, with 212 fully validated completed responses (84.8% response rate). The data was collected and statistically analyzed. The study sheds light on the current situation of endodontic care in Tripoli, Libya, highlighting both progress and ongoing problems. While many dentists use current techniques, such as electronic equipment to evaluate root canal length (81%) and newer bioceramic sealants (40%), significant gaps exist. For example, only 63% of practitioners habitually utilize rubber dams, a vital step in infection management, and antibiotics are frequently provided inadvertently (9% for pain alone). Traditional treatments, such as cold fillings for canal sealing (43%), remain superior to newer methods, while diagnostic processes, such as canal identification (60% rely solely on visual inspection), are variable. These worries, together with common errors in determining canal length (26%) and sealing canals (20%), lead to a compelling need for training, especially because over half of the dentists questioned are young (57% with ≤5 years' experience). To fill these gaps, we recommend hands-on workshops on advanced instruments (e.g., magnification devices), updated infection control measures, and more specific antibiotic use guidelines. By resolving these issues, Tripoli's dentistry community may better match worldwide standards, resulting in safer, higher-quality care for patients.